STUDI SYSTEMATIC LITERATUR REVIEW TENTANG PERAN KOMITE MADRASAH DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN - Sri Atin; Muftahatus Saadah; Anelda Ultavia; Widya Nurhafni Zulfa Purba; Eka Putri Ningsih (STKIP Pesisir Selatan, 2023)
Improving the quality of education is inseparable from the support and cooperation of madrasahs with all elements of stakeholders, including the madrasah committee. This research intends to examine the Madrasah Committee’s role in improving the quality of Islamic Education. Researchers used the Systematic Literature Review (SLR) method. Data collection focused on the results of scientific research on the role of madrasah committees in improving the quality of education published from 2010-2022. Three Research Questions were determined in this study with the final results: (RQ 1) the low quality of education, the lack of infrastructure, and the low quality of human resources in the management of madrasas are the underlying reasons for optimizing the role of the madrasah committee. (RQ 2) the role of the madrasah committee is still not optimal. This is caused by the lack of awareness of the principal and stakeholders of the importance of committees, so they are not empowered. (RQ 3) the madrasa committee plays a role in providing consideration, support, supervision, and mediator between madrasas and the community in a joint effort to improve the quality of education.